Breast reconstruction after mastectomy : a survey of surgeons' and patients' perception - Ishak, Ariffuddin (2018)
Background Breast reconstruction post-mastectomy is important in breast cancer care. Methodology A cross-sectional study was designed to assess surgeons’ and patients’ perceptions towards breast reconstruction. Questionnaires were distributed to all general and breast surgeons in East Coast Malaysia’s general and teaching hospitals and Hospital Kuala Lumpur (n=40), post-mastectomy patients with (n=66) and without breast reconstruction (n=291) from Hospital Universiti Sains Malaysia (HUSM) and Hospital Raja Perempuan Zainab II (HRPZ II). Response rates were 82.5% surgeons (n=33), 95.4% patients with reconstruction (n=63) and 95.5% patients without reconstruction (n=278). Result Data from 30 surgeons (3 excluded as 1 surgeon no longer treating breast diseases and 2 incomplete responses) showed median age of 42 years with 6 years’ experience. Each surgeon saw average 20 new breast cancer cases a year. Most surgeons (86.7%) discussed reconstruction option with patients. However, referral rate was low whereby each surgeon referred only average 4 cases for reconstruction over 3 years. Surgeons’ concern on qualitative outcome increases the likelihood of discussion regarding breast reconstruction with patients (B=4.833, p=0.044). Data from 302 patients (39 exclusion for incomplete responses) showed women with reconstruction were younger (mean age 42 vs 50 years), more were working (69.4% vs 42.2%) and have prior awareness (90.3% vs 44.3%) compared to non-reconstruction group. Commonest reasons for having reconstruction were ‘to feel more balanced’ (92.1%) and ‘surgeon’s strong recommendation’ (92.1%). Prior knowledge on breast reconstruction increases likelihood of reconstruction (OR:5.805, p=0.026). While no surgeons have concern on reconstructive surgery outcome, 21.8% patients were unimpressed with previous outcome seen. Although 70% surgeons felt that patients may not be interested in reconstruction, only 37.9% patients with prior awareness claim to have no interest. Conclusion The study’s low reconstruction rate (20.6%) may be attributed to low referral. Surgeons’ hypothetical criticisms may play some role in the referral rate. Patients’ likelihood to undergo reconstruction with surgeons’ recommendation and prior awareness were reflective of surgeons’ strong influence on patient. Thus clarification on surgeons’ hypothetical criticisms may conceivably increase the reconstructive surgery rate.